EFFECTIVENESS OF FOOD SECURITY POLICIES IN IBSA AND BANGLADESH - Nirmala, V.; Shaurav, Kumar (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
The paper examines food security in terms of its three basic indicators, viz., availability, accessibility and absorption, across IBSA countries and Bangladesh, which together account for nearly a quarter of the worldâs population and more than one-third the undernourished. It also analyses the determinants of prevalence of food inadequacy in these countries. The study is based on data drawn from FAOSTAT, World Development Indicators (World Bank) and Global Food Security Index 2016 for the period 1990-2016. The objectives of the study have been analysed using ratios, percentages, simple average and multiple regressions. The results of the study indicate Brazil to be leading in achievement of the three indicators of food security indicators, whereas India and Bangladesh lag behind in most of the parameters. The determinants of prevalence of food inadequacy revealed that while increase in GDP per capita significantly reduced food inadequacy, growth in population significantly increased it in Brazil. Value of food production and targeted policies ensuring food security emerged as the most significant factors reducing prevalence of food inadequacy in most of the selected countries. The study recommends increasing food production and effective implementation of the food security policies by the four countries. Above all, these countries could also benefit from sharing each othersâ best practices.